A new species of the surgeonfish genus †Caprovesposus (Acanthuridae) from the Lower to Middle Miocene of the North Caucasus, Russia - Bannikov, Alexandre F.; Tyler, James C.; Tyler, Diane M. (Zootaxa, 2025)
A new species of fossil surgeonfish, †Caprovesposus daniltshenkoi sp. nov., is described based upon two specimens from the terminal Maikopian (upper Lower to lower Middle Miocene; not less than 15 mya) in the northwestern Caucasus. The specimens were excavated from brownish gray clays in the bank of the Pshekha River in the Krasnodar Region of Apsheronsk District, Russia. Both specimens are in the acronurus presettlement stage of development and are placed within the formerly monotypic genus †Caprovesposus based upon their possession of vertically elongated, needle-like scales on the body. They differ from the Oligocene †Caprovesposus parvus Daniltshenko, 1960 in (1) lacking serrations on the frontal, mesethmoid, preopercle, and basipterygium; and (2) having the vertically elongated, needle-like scales only on the anterior and middle portions of the body, rather than on the entire body. Three additional, previously collected specimens from the Caucasus and Crimea are referred to the new species.